Paneth cell dysfunction in radiation injury and radio-mitigation by human α-defensin 5 - Shukla, Pradeep K.; Rao, Roshan G.; Meena, Avtar S.; Giorgianni, Francesco; Lee, Sue Chin; Raju, Preeti; Shashikanth, Nitesh; Shekhar, Chandra; Beranova, Sarka; Balazs, Louisa; Tigyi, Gabor; Gosain, Ankush; et al. (Frontiers in Immunology, 2023)
The mechanism underlying radiation-induced gut microbiota dysbiosis is undefined. This study examined the effect of radiation on the intestinal Paneth cell α-defensin expression and its impact on microbiota composition and mucosal tissue injury and evaluated the radio-mitigative effect of human α-defensin 5 (HD5).Methods: Adult mice were subjected to total body irradiation, and Paneth cell α-defensin expression was evaluated by measuring α-defensin mRNA by RT-PCR and α-defensin peptide levels by mass spectrometry. Vascular-to-luminal flux of FITC-inulin was measured to evaluate intestinal mucosal permeability and endotoxemia by measuring plasma lipopolysaccharide. HD5 was administered in a liquid diet 24 hours before or after irradiation. Gut microbiota was analyzed by 16S rRNA sequencing.Intestinal epithelial junctions were analyzed by immunofluorescence confocal microscopy and mucosal inflammatory response by cytokine expression. Systemic inflammation was evaluated by measuring plasma cytokine levels.Results: Ionizing radiation reduced the Paneth cell α-defensin expression and depleted αdefensin peptides in the intestinal lumen. α-Defensin down-regulation was associated with the timedependent alteration of gut microbiota composition, increased gut permeability, and endotoxemia.Administration of human α-defensin 5 (HD5) in the diet 24 hours before irradiation (prophylactic) significantly blocked radiation-induced gut microbiota dysbiosis, disruption of intestinal epithelial tight junction and adherens junction, mucosal barrier dysfunction, and mucosal inflammatory response. HD5, administered 24 hours after irradiation (treatment), reversed radiation-induced microbiota dysbiosis, tight junction and adherens junction disruption, and barrier dysfunction. Furthermore, HD5 treatment also prevents and reverses radiation-induced endotoxemia and systemic inflammation.Conclusions: These data demonstrate that radiation induces Paneth cell dysfunction in the intestine, and HD5 feeding prevents and mitigates radiation-induced intestinal mucosal injury, endotoxemia, and systemic inflammation.